Aspekte van vernuwing in die Afrikaanse leksikografie: Standaard- en pedagogiese woordeboeke as barometer - Beyer, Herman L.; Louw, Phillip A. (Lexikos, 2022)
Innovative Aspects of Afrikaans Lexicography: Standard and Pedagogical Dictionaries as Barometer. The aim of this contribution is to offer an overview of the areas of most significant innovation in the Afrikaans lexicography over the past two decades, with specific reference to standard and pedagogical dictionaries, since they represent the typological categories in which most development is visible. However, reference will also be made to other dictionary types and contexts where relevant. Firstly, the current state of affairs with regard to the Afrikaans lexicography will be outlined in terms of existing lexicographic products. Secondly, some comments will be offered on the professionalisation of Afrikaans lexicography — a topic which has not really been dealt with in metalexicographical research. The roles of the Bureau of the Woordeboek van die Afrikaanse Taal and commercial dictionary publishers will also be highlighted. Thereafter, secondary and specific lexicographic processes will be discussed, with reference to corpus lexicography and lemma selection, macrostructural innovation, and microstructural innovation. The discussion of the latter will include integrated microstructures in bilingual dictionaries, lexicographic definitions in monolingual dictionaries, cotext entries, and aspects of grammatical data. The state of affairs and future of the Afrikaans e-lexicography will also be addressed. Finally, some comments on special dictionaries will be offered. Keywords: commercial lexicography, corpus lexicography, e-lexicography, explanatory dictionary, lexicographic definition, macrostructure, microstructure, pedagogical lexicography, school dictionary, translation dictionary